The Policy Making on Venezuelan Migratory Policies in Peru 2017-2022: Processes, Bifurcation Points and Drivers - Arroyo-Laguna, Juan; Knipper, Michael; Krannich, Sascha; Varas, Paula Estefanía (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2025)
This study examines Peruvian public policies on Venezuelan migration, identifying factors influencing their formulation and implementation while uncovering their behavioral patterns. Using a qualitative approach based on process tracing and thematic analysis of official documents, media narratives, and statistical data, the research identifies three phases of migration policy: (1) open-door policies, (2) securitization and restriction, and (3) invisibilization and normalization of irregular migration. These phases reveal a disconnect between political rhetoric and practical outcomes, with calculated tolerance for policy non-enforcement and migrant integration delegated to civil society and international organizations. The findings highlight incoherent migration policies marked by legal non-compliance, omission as a strategy, and limited state intervention. These dynamics are driven by advocacy coalitions excluded from decision-making, strained executive-legislative relations, and media-influenced public opinion. The study’s originality lies in its innovative combination of process tracing and thematic analysis to explain policy dynamics in contexts of institutional fragility.